Gambaran Penggunaan Obat Pada Pasien Diabetes Mellitus Tipe 2 DI Intalasi Rawat Jalan RS dr. Oen Solo Baru Periode Januari-Juni 2023 - Irfan Al Fahmi; Risma Sakti Pambudi; Khotimatul Khusna (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2024)
Diabetes mellitus (DM) is a widespread health problem and continues to increase every year. Management of DM involves implementing a healthy lifestyle, increasing physical activity, and pharmacological therapy. The aim of this research was to determine the description of drug use in patients with type 2 diabetes mellitus in the outpatient installation of Dr. Hospital. Oen Solo Baru for the period January-June 2023. This research is a non-experimental descriptive research design where data is collected retrospectively. Data analysis uses quantitative research which is presented in the form of a table of number of cases and percentage (%). The number of samples in this study was 100 medical record data. The results of the study showed that there were 5 types of antihyperglycemia drugs used, namely the Sulfonylurea group with (42%), Biguanid (28%), Insulin (12%), DPP-4 Inhibitors (10%), and α-glucosidase Inhibitors (8%) . The conclusion of this study is that the most frequently used antihyperglycemia drugs are sulfonylureas (42%) and the least frequently used are a-gluoxidase inhibitors (8%).